Purwarupa Robot Lengan dengan Mit App Inventor untuk Memilah Barang Berdasarkan Ukuran Tinggi dan Berat Berbasis Internet of Things - aradea, tomi; Thalib, Farid (LPPM STIA Lancang Kuning Dumai, 2024)
At this time the industrial world has developed more and more advanced, many types of technology have helped and replaced human activities in the industrial field, one of which is robotics. The utilization of arm robots in industry, especially in moving goods from one place to another by utilizing the grip of the arm robot grip is one of the best innovations. In this tool, Loadcell sensors are used to calculate the weight of goods and ultrasonic sensors to measure the height of goods. The value data from these two sensors will be used as a reference for 4 conditions in moving goods by the robot arm that has been programmed. Each condition of the value of the two sensors that is met will provide a different output to the servo motor. Infrared sensors on each container are used to update the value of the number of items in each container in the database. The Gripper MIT application will display the output in the form of a display of the number of items in each storage container on the user's smartphone. In testing the sensors used to drive the robot to sort the 8 items used, an error percentage of 1.57% was obtained for the Loadcell sensor and -1.87% for the ultrasonic sensor. By testing the infrared sensor on each box to send data to the MIT Gripper application from 8 items tested, the average travel time for sending data is 6.75 seconds